Performance analysis of wireless power transfer using series-to-series topology - Fairul Azhar Abdul Shukor; Ahmed Mohammed Salem Ahmed Alhattami; Nur Ashikin Mohd Nasir; Chockalingam Aravind Vaithilingam (Institute of Advanced Engineering and Science, 2023)
Wireless power transfer (WPT) is a technology used to transmit power using air as it medium of transfer. The function of the WPT is similar to a transformer. The power provided on the primary side will be transferred through air to the secondary side. The performance of the WPT is crucially depends on the air gap length, ???? that separates primary and secondary side. In this paper discusses the performance of WPT using series-to-series topology. The performance of the WPT was estimated using finite element analysis (FEA). During the study, focus was given to effect of turn ratio, a, air gap length, ???? and capacitor value at primary Cp, and secondary, Cs winding to voltage ratio of the WPT. The air gap length, ???? was set to 1 and 2 mm while the capacitors were set depend on the ratio of primary to secondary winding capacitor, Cp/Cs. The WPT performance also being tested under no-load and loaded operation to observed it effect. As a result, the WPT with turn ratio, a at 0.37, air gap length, ???? at 1 mm and ratio of primary to secondary winding capacitor, Cp/Cs at 0.5 produce the best voltage ratio compared to other settings.